Prophylactic Mesh in Primary Stoma Formation to Prevent Parastomal Hernia: A Systematic Review and Meta-Analysis of its Risk and Benefit - Citra Aryanti; Erwin Syarifuddin; Julianus A. Uwuratuw (Dr. Sulaiman Al Habib Medical Journal)
More than 50% of patients living with a stoma will develop a parastomal hernia. Despite many controversies, the use of prophylactic mesh during primary stoma formation is promising. However, there is no standardized consensus for this prophylactic mesh yet. Therefore, this meta-analysis aims to evaluate the outcomes and complications associated with the application of prophylactic mesh in primary stoma formation. Literature search (EMBASE, MEDLINE, PubMed, The Cochrane Library, and Web of Science) was performed to identify randomized controlled trials (RCTs) evaluating the use of prophylactic mesh versus nomesh for stoma. Included studies were assessed and data extracted by two independent reviewers. Parameters studied included the incidence of parastomal hernia and stoma complications (infection, necrosis, need for reoperation, and obstruction). Cochrane’s risk-of-bias assessment tool was used to evaluate the quality of the included studies. Meta-analysis was performed using fixed- and random-effects models in Review Manager 5.3. Overall, 17 RCTs were included in this meta-analysis, comprising a total of 1698 patients. The overall incidence of parastomal hernia was significantly lower in the mesh group than in the control group (risk ratio 0.56, 95% CI 0.42–0.74, P < 0.001, I2 59%), both in the short or long term (P = 0.006 and P = 0.002, respectively). In subgroup analysis of mesh type (biologic or synthetic), mesh placement (sublay or intraperitoneal), and surgical approach (open or laparoscopy), the rates of parastomal hernia were significantly lowerin the mesh group than in the control group. No significant differences were observed between groups in terms of stoma infection (P = 0.57), stoma necrosis (P = 0.66), need for reoperation (P = 0.84), and intestinal obstruction (P = 0.52). Thus, this meta-analysis suggests that prophylacticmesh in stoma formation reduces the incidence of parastomal herniation and is safe to perform, with complication rates similar to those in the control group.